2001
DOI: 10.1034/j.1600-0412.2001.801107.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgen levels of preeclamptic patients in the third trimester of pregnancy and six weeks after delivery

Abstract: We conclude that higher blood androgen levels measured in preeclamptic patients may be implicated in the pathogenesis of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Although it was found to be within normal range, the level of total testosterone in women with previous SGA infants was significantly higher than those of controls ( P = 0.01). This result is consistent with the evidence of augmented androgen levels during and after pregnancy in women with preeclampsia and gestational hypertension 35,36 . However, the lack of independent association with FMD seems to suggest that testosterone cannot be considered a significant cardiovascular risk factor in these women.…”
Section: Discussionsupporting
confidence: 89%
“…Although it was found to be within normal range, the level of total testosterone in women with previous SGA infants was significantly higher than those of controls ( P = 0.01). This result is consistent with the evidence of augmented androgen levels during and after pregnancy in women with preeclampsia and gestational hypertension 35,36 . However, the lack of independent association with FMD seems to suggest that testosterone cannot be considered a significant cardiovascular risk factor in these women.…”
Section: Discussionsupporting
confidence: 89%
“…Several authors [15,16] reported high androgen levels in women with pre-eclampsia. In fact, androgens could mediate hemodynamic changes underlying pre-eclampsia development by inducing a state of sympathetic hyperactivity and vascular hyperactivity [20].…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we elected to use this dosing regimen, since it caused a 2-fold increase in circulating maternal testosterone levels [17] similar to that observed in human pregnancies complicated with fetal growth inhibition [6-10]. Because an increase in testosterone levels during the later stage of pregnancy was shown to be associated with IUGR [5] and preeclampsia [31,32], we chose this time period (GD 15-19) of TP treatment in pregnant rats.…”
Section: Methodsmentioning
confidence: 99%